Peran Guru dalam Menanamkan Nilai-Nilai Akhlak kepada Anak Berkebutuhan Khusus (ABK) Tunanetra di Sekolah Luar Biasa (SLB)-A Pembina Nasional Jakarta - RA, Anggun Nurjannah; Sodiq, Akhmad (Kopertais Wilayah I DKI Jakarta dan Banten, 2025)
This research is motivated by educational problems, especially Islamic religious education for Children with Special Needs (ABK), especially the blind, which are still not maximally given. In addition, blind people in Indonesia occupy the first level in Asia and second level in the world. This study aimed to analyze the role of teachers in instilling moral values in blind children with special needs (ABK) at Special Schools (SLB)-A Pembina Nasional Jakarta. The results of the study show the role of Islamic religious education teachers in instilling moral values in visually impairments at the SLB-A Pembina Jakarta National Level by acting as educators, teachers, directors, and trainers. In carrying out their role, the teacher faced obstacles in obtaining learning resources, visual aids as learning media, and the physical and emotional conditions of ABK. Therefore, it requires strong physical and spiritual readiness for the teacher so that he/she can carry out his/her role properly. The implication of this research is that it is necessary to carry out evaluations and policies to provide learning resources and visual aids so that the teacher's role can be carried out better.